2020
DOI: 10.1038/s41598-020-66760-w
|View full text |Cite
|
Sign up to set email alerts
|

Controller synthesis and clinical exploration of wearable gyroscopic actuators to support human balance

Abstract: Gyroscopic actuators are appealing for wearable applications due to their ability to provide overground balance support without obstructing the legs. Multiple wearable robots using this actuation principle have been proposed, but none has yet been evaluated with humans. Here we use the GyBAR, a backpack-like prototype portable robot, to investigate the hypothesis that the balance of both healthy and chronic stroke subjects can be augmented through moments applied to the upper body. We quantified balance perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 112 publications
(148 reference statements)
1
24
0
Order By: Relevance
“…We investigate a possible application of the proposed clutch design a wearable balance assistance device, as previously described in [14], [15]. This device contains gyroscopic actuators in a backpack-like construction.…”
Section: F Design Example: Safety Clutch For a Wearable Gyroscopic Balance Assistance Devicementioning
confidence: 99%
See 1 more Smart Citation
“…We investigate a possible application of the proposed clutch design a wearable balance assistance device, as previously described in [14], [15]. This device contains gyroscopic actuators in a backpack-like construction.…”
Section: F Design Example: Safety Clutch For a Wearable Gyroscopic Balance Assistance Devicementioning
confidence: 99%
“…Therefore, we optimize the geometry to find the least sensitive configuration. We also present a design example based on the theoretical requirements for a gyroscopic balance assistance device [14], [15], [18]. In Section III, the estimated performance of an electroadhesive clutch based on the proposed design is compared to SEPAC RFTC-320 electromagnetic clutches, which currently deliver industryleading torque-to-mass and torque-to-power ratios [10], [24].…”
Section: Introductionmentioning
confidence: 99%
“…A wearable backpack-like system capable of exerting recovery forces based on an actuated gimbal mechanism and a flywheel was proposed in [13]. The prototype was later tested on humans with promising results [14]. Nevertheless, the main limitation of this prototype is its low maximum payload, which may make it impractical for long-term use.…”
Section: Introductionmentioning
confidence: 99%
“…Contrarily, intuitive feedback can be provided by providing opposing forces or torques that correct the movement of the user. There are solutions such as the GyroGlove™ that helps reduce hand tremors (Panisse et al, 2016), or the GyBAR that helps with balance issues (Lemus et al, 2020).…”
Section: Augmented Movement Feedbackmentioning
confidence: 99%
“…The GyBAR is a gyroscope installed into a backpack (Lemus et al, 2020), and has been shown to improve the user's ability to walk further on a thin beam, and also standing balance for persons with stroke.…”
Section: Augmented Movement Feedbackmentioning
confidence: 99%